Sulfur-doped graphene quantum dots as a novel fluorescent probe for highly selective and sensitive detection of Fe(3+) - Li, Shuhua; Li, Yunchao; Cao, Jun; Zhu, Jia; Fan, Louzhen; Li, Xiaohong (Analytical chemistry (Washington), 2014)
Sulfur-doped graphene quantum dots (S-GQDs) with stable blue-green fluorescence were synthesized by one-step electrolysis of graphite in sodium p-toluenesulfonate aqueous solution. Compared with GQDs, the S-GQDs drastically improved the electronic properties and surface chemical reactivities, which exhibited a sensitive response to Fe(3+). Therefore, the S-GQDs were used as an efficient fluorescent probe for highly selective detection of Fe(3+). Upon increasing of Fe(3+) concentration ranging from 0.01 to 0.70 μM, the fluorescence intensity of S-GQDs gradually decreased and reached a plateau at 0.90 μM. The difference in the fluorescence intensity of S-GQDs before and after adding Fe(3+) was proportional to the concentration of Fe(3+), and the calibration curve displayed linear regions over the range of 0-0.70 μM. The detection limit was 4.2 nM. Finally, this novel fluorescent probe was successfully applied to the direct analysis of Fe(3+) in human serum, which presents potential applications in clinical diagnosis and may open a new way to the design of effective fluorescence probes for other biologically related targets.